2004
DOI: 10.1128/iai.72.6.3179-3186.2004
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Expression and Cytokine Responses in the Human Urinary Tract Mucosa

Abstract: Mucosal pathogens trigger a local innate host response by activating epithelial cells. Bacterial adherence and Toll-like receptor 4 (TLR4) signaling have been implicated as key events in this process. This study addressed the molecular basis of the epithelial response to gram-negative infection in the human urinary tract. Mucosal biopsies were obtained from kidneys, ureters, and bladders of patients undergoing urinary tract surgery, and epithelial TLR4 and CD14 expression was examined by immunohistochemistry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
182
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(189 citation statements)
references
References 47 publications
3
182
1
3
Order By: Relevance
“…Recent studies using the hemopoietic chimeric Lps n and Lps d mice demonstrated that bladder epithelial cells (19), as well as intrinsic renal epithelial cells (20), contribute together with bone marrow-derived cells to the initiation of antibacterial immunity. Murine and human renal tubule cells express some of the TLR expressed in hemopoietic cells and secrete chemokines upon LPS stimulation (21,22). In addition, TLR2 and TLR4 have been shown to be up-regulated in the distal nephron of inflamed, postischemic, reperfused kidneys (23).…”
Section: Renal Collecting Duct Epithelial Cells React Tomentioning
confidence: 99%
“…Recent studies using the hemopoietic chimeric Lps n and Lps d mice demonstrated that bladder epithelial cells (19), as well as intrinsic renal epithelial cells (20), contribute together with bone marrow-derived cells to the initiation of antibacterial immunity. Murine and human renal tubule cells express some of the TLR expressed in hemopoietic cells and secrete chemokines upon LPS stimulation (21,22). In addition, TLR2 and TLR4 have been shown to be up-regulated in the distal nephron of inflamed, postischemic, reperfused kidneys (23).…”
Section: Renal Collecting Duct Epithelial Cells React Tomentioning
confidence: 99%
“…Epithelial cells must be protected from constant TLR activation by commensals and their PAMP, in order for mucosal integrity to be maintained. The epithelial cells thus lack co-receptors like CD14 [6][7][8][9][10][11], and in addition, commensals have been suggested to actively suppress epithelia responses through NF-jB [12,13]. Yet, mucosal pathogens evoke rapid TLR4-dependent responses at mucosal sites, suggesting that alternative ligands and receptors might be involved in mucosal TLR activation.…”
mentioning
confidence: 99%
“…Type 1 fimbriae are proinflammatory, stimulating release of IL-6, IL-8, and tumor necrosis factor ␣, and they act synergistically with other bacterial products such as lipopolysaccharide (8)(9)(10)(11)(12). The adhesin is sufficient for invasion of uroepithelial cells and may contribute to the etiology of the chronic inflammatory diseases, Crohn's disease, and interstitial cystitis (13)(14)(15)(16).…”
mentioning
confidence: 99%